INTERVENSI PSIKOLOGIS UNTUK PENGENTASAN WANITA TUNA SUSILA Studi Kasus "Zaniyah" Resos Mrican YogyakarTA - Khoiruddin Bashori (LP3 UMY, 2015)
Prostitution is a complex social pathologgt, wilh interrektted causes so lhat lhere is no single independenl faclot lhot can be identified as the main cause. Consequently, in solving the prostitution problem interdisciplinary approach should be employed. This research is basically a psychologica! inlenentian to a prostitute u,ho has alreody been in her position for approximately 2 yeors. The intervention was inlended lo give the object some sort offeelings thttt there is someone who pays atlention, somebodywho can talk to, and one who will help overcome her problems. It is expected lhal the objecl oflhe research feel secure and evenlually can be advised to reach a higher objeclive, far more than simply physical needs.